2018
DOI: 10.1111/njb.01617
|View full text |Cite
|
Sign up to set email alerts
|

Effects of seed colour heterogeneity on germination behaviour of the desert plant Lotononis platycarpa (Fabaceae)

Abstract: We aimed to determine the ecological role of three seed morphs observed for the first time in a desert population of Lotononis platycarpa (Fabaceae), with respect to their germination requirements. Seeds sorted by seed coat colour (olive green, orange and brown) were germinated under laboratory conditions under two photoperiods (12/12‐h light and continuous dark) and three alternating temperature regimes (15/25, 20/30, 25/35°C). We found that the three distinct seed types differ in their seed mass, germination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…(1982). Tal comportamiento se relaciona con el color de la semilla, ya que semillas de testa obscura liberan taninos y compuestos oxidativos que afectan la germinación (Rahman y McVetty, 2011;Gairola et al, 2018). De lo anterior, Bradford (1990) menciona que semillas de testa clara son más rápidas en imbibición, tal como se observa en el comportamiento de Rosita y Nieve en comparación a Uva.…”
Section: Resultados Y Discusiónunclassified
“…(1982). Tal comportamiento se relaciona con el color de la semilla, ya que semillas de testa obscura liberan taninos y compuestos oxidativos que afectan la germinación (Rahman y McVetty, 2011;Gairola et al, 2018). De lo anterior, Bradford (1990) menciona que semillas de testa clara son más rápidas en imbibición, tal como se observa en el comportamiento de Rosita y Nieve en comparación a Uva.…”
Section: Resultados Y Discusiónunclassified
“…seed and optimal germination would occur if seeds were sown at or near soil surface. Gairola, et al (2017) [35] reported seeds of Lotononisplatycarpa (Fabaceae) germinated to higher percentage under light condition than in total darkness. Additionally, seed mass and shape have also been shown to be correlated to germination light requirement and soil seed bank formation for other taxa [31,32].…”
Section: Sensitivity To Light Presencementioning
confidence: 99%
“…The role of light in seed germination is also strongly linked to seed mass and shape, which limits seed burial depth that will permit seed germination and seedling emergence [31,32]. The concept of the role of light on germination has been explored on some wild species and vegetables [33][34][35][36][37]. The knowledge of the role of light on germination is important in propagation and understanding germination ecology of wild germplasm [9].…”
mentioning
confidence: 99%
“…Second, quantifying the relative riskiness of multiple seed heteromorphic strategies allows us to compare strategies to determine which ones minimize risk most effectively. This is significant when multiple solutions are possible to the model of Venable ( 1985 )—such as when more than two morphs are produced, and therefore more than one combination of seed morphs can realize the same geometric fitness (e.g., as in Gairola et al, 2017 ). Third, the quantification of risk may also provide a useful basis by which to compare the riskiness of vegetative and sexual reproduction in seed plants.…”
Section: Introductionmentioning
confidence: 99%